2002
DOI: 10.1001/archpedi.156.6.556
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adolescent Girls With Polycystic Ovary Syndrome

Abstract: Adolescents with PCOS experience lower HRQL compared with healthy adolescents. Polycystic ovary syndrome and perceived severity of illness negatively affect HRQL in adolescents. This study suggests a need to develop interventions to reduce the distress that patients with PCOS may face as adolescents and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 21 publications
7
108
0
6
Order By: Relevance
“…Estos autores señalan un posible efecto de la intervención médica en sus vidas, ya que posterior al tratamiento encontraron mejoría en las mediciones realizadas. Sin embargo, los resultados señalan que no existe relación entre severidad clínica de la enfermedad y calidad de vida, lo que estaría indicando que es la percepción que las adolescentes tienen de su enfermedad lo que impacta en forma negativa la CVRS (2).…”
Section: Análisis Del Temaunclassified
See 1 more Smart Citation
“…Estos autores señalan un posible efecto de la intervención médica en sus vidas, ya que posterior al tratamiento encontraron mejoría en las mediciones realizadas. Sin embargo, los resultados señalan que no existe relación entre severidad clínica de la enfermedad y calidad de vida, lo que estaría indicando que es la percepción que las adolescentes tienen de su enfermedad lo que impacta en forma negativa la CVRS (2).…”
Section: Análisis Del Temaunclassified
“…La evaluación de la calidad de vida de las mujeres jóvenes con patología crónica, como el Síndrome de Ovario Poliquístico (SOP), se ha planteado de gran relevancia (2).…”
Section: Introductionunclassified
“…Adolescent girls with PCOS, similar to adult PCOS are at an increased risk of developing insulin resistance, type 2 diabetes mellitus and metabolic syndrome (glucose intolerance, dyslipidemia, hypertension and central obesity). 8 The symptoms and signs that define this condition often overlap with the physiological changes of the reproductive axis that occur in normal girls during this period. 9 Altered life style that includes high calorie diet and lack of exercise has been well recognized as a exacerbating factor.…”
Section: Introductionmentioning
confidence: 99%
“…10 Association between stress and PCOS has also been documented. 8,11 Obesity exacerbates insulin resistance and favours the progression from impaired glucose tolerance to diabetes in these patients. The familial clustering of women with PCOS suggests that heredity is implicated in the origin of the syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PCOS has a negative impact on the quality of life of adult women but also of adolescent girls with this condition [3][4][5][6][7]. Jones et al [5] found emotional and social functioning more affected than the areas of physical functioning.…”
Section: Introductionmentioning
confidence: 99%